Methods for identifying subject-specific abnormalities in neuroimaging data - Mayer, Andrew R.; Bedrick, Edward J.; Ling, Josef M.; Toulouse, Trent; Dodd, Andrew (Human brain mapping, 2014)
Algorithms that are capable of capturing subject‐specific abnormalities (SSA) in neuroimaging data have long been an area of focus for diverse neuropsychiatric conditions such as multiple sclerosis, schizophrenia, and traumatic brain injury. Several algorithms have been proposed that define SSA in patients (i.e., comparison group) relative to image intensity levels derived from healthy controls (HC) (i.e., reference group) based on extreme values. However, the assumptions underlying these approaches have not always been fully validated, and may be dependent on the statistical distributions of the transformed data. The current study evaluated variations of two commonly used techniques (“pothole” method and standardization with an independent reference group) for identifying SSA using simulated data (derived from normal, t and chi‐square distributions) and fractional anisotropy maps derived from 50 HC. Results indicated substantial group‐wise bias in the estimation of extreme data points using the pothole method, with the degree of bias being inversely related to sample size. Statistical theory was utilized to develop a distribution‐corrected z‐score (DisCo‐Z) threshold, with additional simulations demonstrating elimination of the bias and a more consistent estimation of extremes based on expected distributional properties. Data from previously published studies examining SSA in mild traumatic brain injury were then re‐analyzed using the DisCo‐Z method, with results confirming the evidence of group‐wise bias. We conclude that the benefits of identifying SSA in neuropsychiatric research are substantial, but that proposed SSA approaches require careful implementation under the different distributional properties that characterize neuroimaging data. Hum Brain Mapp 35:5457–5470, 2014. © 2014 Wiley Periodicals, Inc.